Use of the one-legged hyperextension test and magnetic resonance imaging in the diagnosis of active spondylolysis. Issue 11 (15th September 2006) - Masci, L; Pike, J; Malara, F; Phillips, B; Bennell, K; Brukner, P
Abstract : Background: Active spondylolysis is an acquired lesion in the pars interarticularis and is a common cause of low back pain in the young athlete. Objectives: To evaluate whether the one-legged hyperextension test can assist in the clinical detection of active spondylolysis and to determine whether magnetic resonance imaging (MRI) is equivalent to the clinical gold standard of bone scintigraphy and computed tomography in the radiological diagnosis of this condition. Methods: A prospective cohort design was used. Young active subjects with low back pain were recruited. Outcome measures included clinical assessment (one-legged hyperextension test) and radiological investigations including bone scintigraphy (with single photon emission computed tomography (SPECT)) and MRI. Computed tomography was performed if bone scintigraphy was positive. Results: Seventy one subjects were recruited. Fifty pars interarticulares in 39 subjects (55%) had evidence of active spondylolysis as defined by bone scintigraphy (with SPECT). Of these, 19 pars interarticulares in 14 subjects showed a fracture on computed tomography. The one-legged hyperextension test was neither sensitive nor specific for the detection of active spondylolysis. MRI revealed bone stress in 40 of the 50 pars interarticulares in which it was detected by bone scintigraphy (with SPECT), indicating reduced sensitivity in detecting bone stress compared with bone scintigraphy (p  =  0.001). Conversely, MRI revealed 18 of the 19 pars interarticularis fractures detected by computed tomography, indicating concordance between imaging modalities (p  =  0.345). There was a significant difference between MRI and the combination of bone scintigraphy (with SPECT)/computed tomography in the radiological visualisation of active spondylolysis (p  =  0.002). Conclusions: These results suggest that there is a high rate of active spondylolysis in active athletes with low back pain. The one-legged hyperextension test is not useful in detecting active spondylolysis and should not be relied on to exclude the diagnosis. MRI is inferior to bone scintigraphy (with SPECT)/computed tomography. Bone scintigraphy (with SPECT) should remain the first-line investigation of active athletes with low back pain followed by limited computed tomography if bone scintigraphy is positive.